Establishing a Luminescence-Based Chronostratigraphy for the Last Glacial-Interglacial Cycle of the Loess-Palaeosol Sequence Achajur (Armenia) - Lomax, Johanna; Wolf, Daniel; Wolpert, Urs Tilmann; Sahakyan, Lilit; Hovakimyan, Hayk; Faust, Dominik; Fuchs, Markus (Frontiers in Earth Science, 2021)
In this paper we establish a luminescence-based chronology of the loess-palaeosol-section Achajur in northern Armenia. The section comprises three prominent pedocomplexes with intercalated loess units, probably spanning at least three glacial-interglacial cycles. Due to erosional disturbance in the lower part of the section, only the upper part was dated, with two samples below the P-1 pedocomplex, and 11 samples further above. Dating was carried out on the polymineral fine grain fraction, mainly using a non-fading corrected pIR-IRSL-225 protocol. To support the reliability of the ages, additional quartz fine grain ages and polymineral pIR-IRSL-290 ages were determined. Together with fading tests, these additional ages show that a fading correction is not necessary for most of the samples. The resulting chronology is in line with the MIS-based climate stratigraphy, i.e. loess deposition during glacials and stadials and soil formation during interglacials and interstadials. A prominent tephra within the L-2 loess is at least ca. 140 ka old and may be derived from Lake Nemrut in Turkey. For interpretation of the palaeoclimatic significance of the results, the loess section is compared to further proxy data found at Lake Van, Lake Urmia and in other loess sections from nearby sites.